Peran Cost Recovery pada Sektor Minyak dan Gas Bumi dalam Mendorong Pembangunan Ekonomi Nasional - Edy Soesanto; Ridwan Zaidaan; Shidqul Azaim Ahiraf (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
Cost Recovery is a vital element in production sharing contracts (PSCs) within the oil and gas sector, allowing contractors to recover costs incurred during exploration and production through revenues generated from oil and gas production. This mechanism has a direct impact on the sustainability of operations and the management of natural resources, which in turn plays a critical role in supporting the national economy.This study aims to analyze the role and contribution of the cost recovery scheme in enhancing Indonesia's economic development, focusing on optimizing state revenue, increasing both foreign and domestic investment, and promoting the development of sustainable energy infrastructure. The method used in this study is a literature review, which includes data from journals and published articles.The main findings of the study show that the cost recovery scheme not only functions as an instrument to ensure the sustainability of upstream oil and gas operations but also has a significant impact on other economic aspects. In the context of national economic development, this scheme contributes to increasing state revenue through taxes and royalties, creating jobs, and supporting local economic development in oil and gas-producing regions. Moreover, cost recovery opens up opportunities for technology transfer and enhances human resource capacity in the energy sector.